A facile procedure to modify filter paper for oil–water separation. Issue 48 (13th June 2017) - Tang, Xinde; Shen, Chunli; Zhu, Wenjing; Zhang, Shuai; Xu, Youfu; Yang, Yueqing; Gao, Min; Dong, Fuying
Abstract : A much simpler and broadly applicable dip-coating method using silica nanoparticles and a silane coupler for preparing hydrophobic paper is presented. Abstract : A much simpler and broadly applicable dip-coating method using silica nanoparticles and a silane coupler for preparing hydrophobic paper is presented. Both producing surface hydrophobization without additional surface treatment and increasing the adhesive force between the paper and the coated material can be realized by an almost one-step procedure. The modified filter paper could not only selectively permeate oil from a mixture, but also exhibits superior recyclability, indicating its great potential application in the oil–water separation area.